Spontaneous expulsion of a pulmonary hydatid cyst through bronchial rupture. (October 2018) - Pannu, Ashok Kumar; Golla, Rithvik
The management of a pulmonary echinococcal cyst consists mainly of medical treatment with a scolicidal agent such as albendazole and surgical extirpation. Rarely, a pulmonary cyst may rupture into a bronchus and be spontaneously expelled. This may result in seeding elsewhere in the bronchial tree, or even the alimentary tract, but occasionally, as in our case, may result in a cure.